Structural stability and superior electrochemical performance of Sc-doped LiMn2O4 spinel as cathode for lithium ion batteries. (1st April 2019) - Bhuvaneswari, Subramani; Varadaraju, U.V.; Gopalan, R.; Prakash, Raju
Abstract: Scandium doped LiScx Mn2-x O4 compounds are synthesized by solid-state method, which show single phase with rod-like polyhedron morphology. The Sc-doping decreases the lattice parameter 'a' marginally due to the change in the inter-atomic distance of the metal oxide bonds as confirm by Rietveld refinement. In addition, the expansion of LiO4 tetrahedron and contraction of MnO6 octahedron by ∼0.01 Å upon doping are observed. The Sc2p3/2 peak at 402.5 eV and Sc2p1/2 peak at 407.2 eV in the XPS spectrum of LiSc0.06 Mn1.94 O4 confirms the presence of Sc in the spinel structure. The symmetric stretching of MnO bond of LiSc0.06 Mn1.94 O4 shifts lower value (∼4 cm −1 ) than that of LiMn2 O4 indicating the occupancy of Sc 3+ ion in the octahedral site. The diffusion coefficient value of LiSc0.06 Mn1.94 O4 (1 × 10 −12 cm 2 s −1 ) is one-order higher than that of undoped LiMn2 O4 (1 × 10 −13 cm 2 s −1 ). LiMn2 O4 delivers a discharge capacity of 117 mAhg −1  at 1C with a capacity retention of 74% after 500 cycles, whereas under similar condition LiSc0.06 Mn1.94 O4 delivers a discharge capacity of 114 mAhg −1 with a capacity retention of >90%. LiSc0.06 Mn1.94 O4 also delivers excellent rate capability due to high diffusion coefficient and less charge transfer resistance compared to the parent compound. The structure and morphology of the Sc-doped electrode after 500 cycles remains intact without any formation of Mn-rich agglomeration suggest that the reduction of Mn 2+ ion dissolution as well as Jahn-Teller distortion. Hence LiSc0.06 Mn1.94 O4 can be a potential cathode material for lithium ion batteries. Graphical abstract: Sc-doped LiMn2 O4 spinel by hydrothermal and solid state method shows significant enhancement in cyclic stability and rate capability performance than pristine spinel as cathode in lithium ion batteries.Image 1